2018
DOI: 10.3389/fpsyg.2018.00143
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year-Olds’ and Adults’ Use of Paralinguistic Cues to Overcome Referential Uncertainty

Abstract: An eye-tracking methodology was used to explore adults’ and children’s use of two utterance-based cues to overcome referential uncertainty in real time. Participants were first introduced to two characters with distinct color preferences. These characters then produced fluent (“Look! Look at the blicket.”) or disfluent (“Look! Look at thee, uh, blicket.”) instructions referring to novel objects in a display containing both talker-preferred and talker-dispreferred colored items. Adults (Expt 1, n = 24) directed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Recordings of participants' eye movements showed that listeners already anticipated reference to unknown objects (increase in proportion of fixations to unknown objects) when hearing the filler uh in the disfluent condition (i.e., well before hearing the target). Other studies have since shown the same effect in children as young as 2 years of age (Kidd, White, & Aslin, 2011;Orena & White, 2015;Owens & Graham, 2016;Owens, Thacker, & Graham, 2018;Thacker, Chambers, & Graham, 2018a, 2018b. Adult listeners have also been shown to be able to predict other types of complex referents, such as discourse-new (Arnold, Fagnano, & Tanenhaus, 2003;Arnold, Tanenhaus, Altmann, & Fagnano, 2004;Barr & Seyfeddinipur, 2010), compound (Watanabe, Hirose, Den, & Minematsu, 2008), and low-frequency referents (Bosker, Quené, Sanders, & De Jong, 2014a) upon hearing a disfluent filler uh.…”
mentioning
confidence: 86%
“…Recordings of participants' eye movements showed that listeners already anticipated reference to unknown objects (increase in proportion of fixations to unknown objects) when hearing the filler uh in the disfluent condition (i.e., well before hearing the target). Other studies have since shown the same effect in children as young as 2 years of age (Kidd, White, & Aslin, 2011;Orena & White, 2015;Owens & Graham, 2016;Owens, Thacker, & Graham, 2018;Thacker, Chambers, & Graham, 2018a, 2018b. Adult listeners have also been shown to be able to predict other types of complex referents, such as discourse-new (Arnold, Fagnano, & Tanenhaus, 2003;Arnold, Tanenhaus, Altmann, & Fagnano, 2004;Barr & Seyfeddinipur, 2010), compound (Watanabe, Hirose, Den, & Minematsu, 2008), and low-frequency referents (Bosker, Quené, Sanders, & De Jong, 2014a) upon hearing a disfluent filler uh.…”
mentioning
confidence: 86%
“…Intriguingly, listeners are sensitive to the patterning of filled pauses in speech and use these disfluencies to predict words or descriptions that would not be readily accessible to the talker (Arnold et al, 2003). Studies have shown that filled pauses lead listeners to rapidly anticipate reference to newly learned or difficult to name objects (Arnold et al, 2007; Heller et al, 2015; Morin-Lessard & Byers-Heinlein, 2019), objects with low-frequency names (Bosker et al, 2014), speaker-dispreferred objects (Thacker et al, 2018), or discourse-new objects (Arnold et al, 2003, 2004; Arnold & Tanenhaus, 2011; Barr, 2001; Barr & Seyfeddinipur, 2010; Orena & White, 2015; Owens & Graham, 2016; Yoon & Brown-Schmidt, 2014). Although at first glance these patterns might be explained by a learned association between filled pauses and whether the name for an object is readily accessible, there is evidence that the effects involve more situation-specific factors.…”
Section: The Real-time Processing Of Disfluenciesmentioning
confidence: 99%
“…Moreover, children’s predictive use of disfluencies is not limited to a simple association between disfluency and particular types of referents (e.g., discourse-new referents). Rather, like adults, children make inferences about the possible causes of disfluencies, interpreting them flexibly based on the difficulty a particular speaker should have in naming an object ( Orena and White, 2015 ; Thacker et al, 2018a,b ). To illustrate, Orena and White (2015) introduced 3.5-year-old children to either a knowledgeable speaker who competently named everyday objects, or a forgetful speaker who often could not name ordinary objects.…”
Section: Introductionmentioning
confidence: 99%